Dissecting network externalities in international migration - Michel Beine; Frédéric Docquier; Çağlar Özden (Center for Economic Studies and ifo Institute (CESifo), 2011)
Existing migrant networks play an important role in explaining the size and structure of immigration flows. They affect the net benefits of migration for future migrants by lowering assimilation costs ('self-selection' channel) and increase the probability of potential migrants to obtain a visa through family reunification programs ('immigration policy' channel). This paper presents an identification strategy allowing to disentangle these two channels. Then, it provides an empirical illustration based on US immigration data by metropolitan area and country of origin. First, we show that the overall network externality is strong: the elasticity of migration flows to network size is around one. Second, only a quarter of this elasticity is accounted for by the policy channel. Third, the policy channel was stronger in the nineties than in the eighties due to more generous family reunion program. Fourth, the global elasticity and the policy contribution are much greater for low-skilled migrants.
Keywords: F22; O15; 330; migration; network/diaspora externalities; immigration policy; Einwanderung; Soziales Netzwerk; Network Externalities; Migrationstheorie; Migrationspolitik; Theorie; USA